2015
DOI: 10.1089/neu.2014.3611
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Gene 15 Upregulation Precedes the Development of Blood–Brain Barrier Disruption and Cerebral Edema after Traumatic Brain Injury in Young Mice

Abstract: Recent studies show that myosin light chain kinase (MLCK) plays a pivotal role in development of cerebral edema, a known complication following traumatic brain injury (TBI) in children and a contributing factor to worsened neurologic recovery. Interferon-stimulated gene 15 (ISG15) is upregulated after cerebral ischemia and is neuroprotective. The significant role of ISG15 after TBI has not been studied. Postnatal Day (PND) 21 and PND24 mice were subjected to lateral closed-skull injury with impact depth of 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…While a critical role for type I interferon signaling is recognized in fighting CNS viral infections, type I interferon signaling has received limited study in TBI making the magnitude of the interferon response in our study quite surprising. A small number of interferon-stimulated genes have been individually studied and recognized to increase following TBI [ 41 , 42 ]. More recently, a TBI study demonstrated neuroprotection with deficiency of type I interferon signaling in peripheral, hematopoietic-derived immune cells, whereas a separate TBI study demonstrated improved neurologic function and prevention of tissue loss with global interferon beta (IFN-β) deficiency [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a critical role for type I interferon signaling is recognized in fighting CNS viral infections, type I interferon signaling has received limited study in TBI making the magnitude of the interferon response in our study quite surprising. A small number of interferon-stimulated genes have been individually studied and recognized to increase following TBI [ 41 , 42 ]. More recently, a TBI study demonstrated neuroprotection with deficiency of type I interferon signaling in peripheral, hematopoietic-derived immune cells, whereas a separate TBI study demonstrated improved neurologic function and prevention of tissue loss with global interferon beta (IFN-β) deficiency [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a biochemical link between TBI and ALS is not known. Other reports demonstrating that interferon-stimulated gene 15 (ISG15), a protein of interest in our lab, is elevated in ALS patients (6) and in response to TBI in mice (7) suggests a plausible link between ISG15-TBI-ALS and led us to investigate ISGylation in TBI-exposed ALS veterans.…”
Section: Introductionmentioning
confidence: 92%
“…However, whether ISGylation is elevated and induces proteinopathy in human ALS patients has not been investigated. Notably, ISG15 levels are increased in the brains of mice subjected to TBI (7). TBI due to blast explosions, motor vehicle accidents, and gunshot wounds during war is commonly seen in veterans.…”
Section: Introductionmentioning
confidence: 99%
“…ISG15 is also induced in other physiological and pathological contexts, which reveal it might potentially function beyond restriction infection. Indeed, ISG15 is elevated upon traumatic brain injury (Rossi et al, 2015) and after cerebral focal ischemia (Nakka et al, 2011), where it has a neuroprotective effect as shown by increased mortality, exacerbated infarction and worsened neurologic recovery of ISG15-KO mice when they are subjected to transient middle cerebral artery occlusion (Nakka et al, 2011). Interestingly, ISGylation of hypoxia-inducible factor 1α (HIF-1α) disrupts its dimerization and attenuates HIF-1α-mediated gene expression, resulting in decreased tumor growth (Yeh et al, 2013).…”
Section: Newly Described Isg15 Functionsmentioning
confidence: 99%